Seasonal dynamics of Chironomus transvaalensis populations and the microbial community composition of their egg masses. Issue 24 (10th January 2020) - Sela, Rotem; Halpern, Malka
ABSTRACT: Chironomids ( Diptera ; Chironomidae ) are the most abundant insects in freshwater environments and are considered natural reservoirs of Vibrio cholerae . We monitored the annual dynamics of chironomid populations along with their microbiota in order to better understand host–microbiota interactions. Chironomus transvaalensis populations peaked biannually in August and May–June. The composition of the endogenous bacterial communities of their egg masses clustered in two groups according to the sampling periods August–November and May–July. Nevertheless, a core bacterial community (43%) was present in all egg-mass samples. The most abundant phyla were: Proteobacteria, Firmicutes, Cyanobacteria and Bacteroidetes . The abundance of several genera (e.g. Rheinheimera and Pseudomonas ) was positively correlated with C. transvaalensis population dynamics, while a predator–prey interaction was observed between the relative abundance of Vibrio OTUs and C. transvaalensis population size. Chironomids are known to tolerate toxic and stress conditions, and our results demonstrated that bacterial genera that may protect the insect under these conditions are present in the egg masses. After hatching, the first larval meal is the gelatinous matrix that surrounds the eggs. This meal contains a probiotic consortium that may protect the larva during its metamorphosis. The results provide important insights into the host–microbe interactions of chironomids. Abstract : Chironomus transvaalensis populations peaked biannually while the endogenous bacterial communities of their egg masses clustered in two groups according to the sampling periods August–November and May–July.